(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agricultural Implements manufacturing industries use raw material from the Iron and steel industry to produces agricultural machinery products. If we explore the research done in past, a majority of work has been taken on iron and steel industry regarding the environment. These industries are adversely affecting the environment in manufacturing process. This research has tried to add the link that the agricultural manufacturing industry is taking the raw material from iron and steel industry while the iron and steel industry is affecting the environment in the process of production. For this reason research has also analyzed the relevant reference (objective wise) of manufacturing industries industry in paper. On the basis Literature survey identified the research gap and this research paper proposed the current scenario of agricultural implements manufacturing. An evaluation of the current status of Agricultural Implements manufacturing industries w.r.t their emission of pollutants and their level of significance have been analyzed including EMP plan for industries and government.